Sudden acquired retinal degeneration syndrome may be an acquired primary ciliopathy, phenotypically similar to human Alström and Bardet-Biedl syndromes - Toler, Steven; Abrams, Kenneth; Ward, Daniel (Frontiers in Veterinary Science, 2025)
Sudden acquired retinal degeneration syndrome (SARDS) is an acquired canine disease that presents as rapidly progressive retinal degeneration, often accompanied by polyphagia, weight gain, polydipsia, polyuria, and hyposmia. Alström syndrome (AS) and Bardet-Biedl syndrome (BBS) are rare human autosomal recessive genetic disorders marked by progressive retinopathy, polyphagia, obesity, polydipsia, polyuria, and hyposmia, with varying degrees of phenotypic severity. While the etiology of AS and BBS is partially understood, the cause of acquired SARDS remains elusive. Historically, scientific inquiry has focused on an immunologic insult and/or endocrinopathy as the cause of SARDS. Clinicians have often pointed to these Cushingoid symptoms mentioned above in SARDS patients as evidence of a contributing endocrinopathy. However, systemic cortisol concentrations, both pre- and post-ACTH stimulation, typically do not differ appreciably between normal patients and those with SARDS. Blindness due to photoreceptor degeneration, along with the observed Cushingoid symptoms, may result from dysfunctional or absent primary cilia, as documented in human AS and BBS cases. Recognizing SARDS as a possible acquired ciliopathy may be the first step toward seeking effective treatments.